ACL reconstruction combined with anterolateral structures reconstruction for treating ACL rupture and knee injuries: a finite element analysis - Wang, Huizhi; Yao, Gai; He, Kaixin; Wang, Zimin; Cheng, Cheng-Kung (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: The biomechanical indication for combining anterolateral structures reconstruction (ASLR) with ACL reconstruction (ACLR) to reduce pivot shift in the knee remains unclear. This study aims to investigate knee functionality after ACL rupture with different combinations of injuries, and to compare the effectiveness of ALSR with ACLR for treating these injuries. Methods: A validated finite element model of a human cadaveric knee was used to simulate pivot shift tests on the joint in different states, including 1) an intact knee; 2) after isolated ACL rupture; 3) after ACL rupture combined with different knee injuries or defect, including a posterior tibial slope (PTS) of 20°, an injury to the anterolateral structures (ALS) and an injury to the posterior meniscotibial ligament of the lateral meniscus (LP); 4) after treating the different injuries using isolated ACLR; v. after treating the different injuries using ACLR with ALSR. The knee kinematics, maximum von Mises stress (Max.S) on the tibial articular cartilage (TC) and force in the ACL graft were compared among the different simulation groups. Results and discussion: Comparing with isolated ACL rupture, combined injury to the ALS caused the largest knee laxity, when a combined PTS of 20° induced the largest Max.S on the TC. The joint stability and Max.S on the TC in the knee with an isolated ACL rupture or a combined rupture of ACL and LP were restored to the intact level after being treated with isolated ACLR. The knee biomechanics after a combined rupture of ACL and ALS were restored to the intact level only when being treated with a combination of ACLR and ALSR using a large graft diameter (6 mm) for ALSR. However, for the knee after ACL rupture combined with a PTS of 20°, the ATT and Max.S on the TC were still greater than the intact knee even after being treated with a combination of ACLR and ALSR. The finite element analysis showed that ACLR should include ALSR when treating ACL ruptures accompanied by ALS rupture. However, pivot shift in knees with a PTS of 20° was not eliminated even after a combined ACLR and ALSR.